Images of Palestina in the Poems Li-Bilādinā & Wa Lanā Bilād by Mahmoed Darwish - Fatimah, Siti; Mas’adi, M. Anwar (Mantiqu Tayr: Journal of Arabic Language, 2026)
This research is motivated by the prolonged socio-political conflict experienced by the Palestinian people, which has resulted in displacement, loss of sovereignty, and humanitarian suffering. In this context, literature particularly poetry functions not only as an aesthetic expression but also as a medium of reflection and resistance against oppressive realities. This study aims to reveal the image of Palestine in the poems Li-Bilādinā and Wa Lanā Bilād by Mahmoed Darwish using Alan Swingewood’s sociological approach to literature. This study employs a descriptive qualitative method with a historical-sociological approach to examine the relationship between literary texts and the social, historical, and cultural contexts that underlie them. Data were collected through close reading and note-taking techniques, while data analysis was conducted through three stages: data reduction, comparison of poetic quotations and interpretations from relevant references, and conclusion drawing. The findings indicate that Li-Bilādinā and Wa Lanā Bilād portray Palestine as a sacred yet oppressed land that has lost its sovereignty, identity, and living space due to colonization. In Li-Bilādinā, Palestine is depicted as a holy land marked by suffering, dispossession, and wounded identity, whereas Wa Lanā Bilād presents Palestine as an inner homeland and collective hope that survives in memory despite physical loss. Based on Alan Swingewood's sociological perspective on literature, these two poems reflect three main aspects of the socio-political reality of Palestine, namely territorial and sovereignty conflicts, humanitarian crises resulting from expulsion and violence, and economic crises as a result of structural colonization. Thus, this study confirms that Mahmoed Darwish's work is not merely an aesthetic expression, but a social document that raises awareness of the suffering and struggle of the Palestinian people and calls for the importance of global solidarity for justice and humanity. Therefore, this research contributes to the field of literary sociology by demonstrating the relevance of poetry as a medium for representing socio-political realities and by encouraging further studies on literary works from conflict zones using interdisciplinary perspectives.